The performance of mesoporous magnetite zeolite nanocomposite in removing dimethyl phthalate from aquatic environments. Issue 57 (7th December 2016) - Ahmadi, Ehsan; Kakavandi, Babak; Azari, Ali; Izanloo, Hasan; Gharibi, Hamed; Mahvi, Amir Hossein; Javid, Allahbakhse; Hashemi, Seyed Yaser
Abstract: In this study, magnetic zeolite nanocomposite with an average diameter of 90–100 nm was synthesized through a chemical co-precipitation method, and used for the adsorption of dimethyl phthalate (DMP) from aqueous solution. The surface morphology of the adsorbent was characterized by scanning electron microscope, transmission electron microscopy, energy dispersive X-ray, vibrating sample magnetometer, dynamic light scattering, Brunauer, Emmett, Teller, and X-ray diffraction techniques. Batch system was followed to optimize the conditions for the removal of DMP. The adsorption experiments were carried out in terms of pH, contact time, various concentrations of DMP as well as nanocomposite, and temperature. The results showed that with increase in adsorbent dosage and contact time increased the adsorption efficiency. However, the efficiency decreased by increasing pH and initial DMP concentration. Experimental data were found to fit well with Langmuir isotherm ( R 2  > 0.981) in all the studied temperatures. Adsorption kinetics also showed that the adsorption behavior follows the pseudo-second-order kinetic model ( R 2  > 0.996). Besides, thermodynamic analysis demonstrated that the adsorption process occurs spontaneously and is inherently endothermic. The DMP adsorption efficiency did not change after 10 batch sorption–desorption reactions, indicating the potential application prospect of the synthesized adsorbent in real water treatment.